Spectral Efficient Resource Allocation using Bio-Inspired Algorithm for NOMA Networks (International Journal of Innovative Research in Engineering & Management, 2022)
Today's wireless networks allocate radio  resources to users based on the Orthogonal Multiple  Access (OMA) principle. However, as the number of  users increases, OMA based approaches may not meet the stringent emerging requirements including very high spectral efficiency, very low latency, and massive device  connectivity. Non-Orthogonal multiple access (NOMA)  principle emerges as a solution to improve the spectral  efficiency while allowing some degree of multiple access  interference at receivers. NOMA is fundamentally  different than orthogonal multiple access schemes which  provide orthogonal access to the users either in time,  frequency, code or space. In NOMA, each user operates  in the same band and at the same time where they are  distinguished by their power levels. NOMA uses superposition coding at the transmitter such that the successive interference cancellation (SIC) receiver can  separate the users both in the uplink and in the downlink  channels. This paper analyzes the spectral efficiency of Filter  Bank Multiple Carrier (FBMC) and Universal Filter Multiple Carrier(UFMC) Modulation Schemes with NOMA while considering Orthogonal Quadrature Amplitude Modulation (OQAM) as the modulation scheme and NOMA as the multiple access scheme.
Keywords: Fbmc; Oma; Noma; Ufmc; Oqam; Sic